Planning As a Moral Discourse: Some Ideas For Planning Education in Indonesia - Setiawan, B. (Center for Research and Community Services ITB, 1996)
This paper questions the direction of planning education which is: 1) too oriented toward the practical interest of planning profession; 2) bas ed on the planning perception which is too deterministic and too emphasis on spatial aspect; 3) not fully perceive a more broader role and position of planning in general public; and 4) ignoring the role of planning education as a place for developing planning science. Starting out from the conception that planning is also a “moral discourse”, this paper suggests a “holistic” planning education based on the reality that the thought and activity of planning is not merely a technical rational process, but fu ll of economic, social, and political complexities. Begin by evaluating and clarifying streams in planning theory, this paper then discusses the context and some ideas for the development of planning in developing countries as a whole and in Indonesia, in particular.